Analisis Strategi Pemasaran Terhadap Produk Obat Herbal Secara Online Studi Kasus Pengembangan Usaha “Taman Sringanis” - Aprilia, Natasya; Adrian, Adrian; Permata, Irma Sari (Jurnal Ilmiah Wahana Pendidikan, 2024)
Marketing strategy is one way to win a sustainable competitive advantage for companies that produce goods or services. Marketing strategy planning needs to be carried out by the company to achieve company goals. In the current era of technological advances, marketing can not only be done directly/offline but can also be done indirectly via the internet. We are social data records that around 49.5% of the reasons users actively use the internet in Indonesia are to find out about products and brands. This amount can be an opportunity for business people to market their products online. Taman Sringanis is one of the companies that processes medicinal plants into herbal medicines and herbal medicines in Bogor City. In its marketing activities, the Taman Sringanis company is still experiencing difficulties, because the company only relies on direct sales in offline stores and has not utilized digital as a marketing medium. This research aims to develop appropriate alternative marketing strategies for Herbal Medicine products in Taman Sringanis. The analytical tool used in this research is SWOT analysis, which includes: the IFE Matrix, EFE Matrix, and IE Matrix. The results of the data analysis produced in the IE Matrix can be concluded that Taman Sringanis is in quadrant IV (growth and build), so the alternative that can be chosen is to carry out online promotional activities by utilizing the image and quality of product to increase sales and utilizing the internet by conducting marketing online to reach new market segments.